Respon ODHA terhadap Program Penanggulangan HIV/AIDS - Ngadiyono Ngadiyono (Jurnal Riset Kesehatan, 2015)
The purpose of this research is to study the Response of people living with HIV toward HIV/AIDS prevention program. The research uses qualitative methods with phenomenological type of chronologic. The data analysis is carried out openly, prepared by the method of descriptive content (content analysis). The results of the study show that the response against HIV-positive people, who implemented the program, may be accepted gradually, less variation activities, and still lack of recognition of the idea and role in the activities. Furthermore, they are still dependent. While maladtif response, especially in terms of the activities carried out are still monotonous, so that the individual / group of HIV-positive people are less active. Besides, people with HIV feel no financial gain. Advice is given to implement the programs/policies continuously and consistently. It is also important to enhance the amount/type of activity by combining ideas and increase the participation of people living with HIV to express them.